Aplikasi Perhitungan EOQ (Economic Order Quantity) Persediaan Handphone Pada Outlet Kurnia Cell Teluk Kuantan - Rabby Nazli (RJOCS (Riau Journal of Computer Science), 2018)
Kurnia Cell Teluk Kuantan is a business engaged in the sale of Mobile. For achieving the maximum results, it is necessary to have a change in control of the stock of goods in order to more optimal and efficient management. Therefore your Kurnia Cell Teluk Kuantan requires a mechanism to control inventory stock of goods to control the amount of stock so as not to run out of stock of finished goods unexpectedly. From the results of the implementation and testing of systems , inventory control stock of this item to the store manager , it can be concluded that this system can facilitate the store manager to see the amount of remaining stock of goods in the store . It also can help leaders to make a decision that will be taken to the progress of his shop.